Finansinio užstato pinigais kvalifikavimo problematika - Juzikienė, Renata (Teisė, 2021)
The article analyzes the distinctive features of the financial collateral in cash as a special form of commercial charge. The analysis is relevant for its legal qualification and distinguishment from another form of charge established in the Civil Code – the pledge of monetary funds in the bank account of a pledgor. A proper legal classification of the collateral in cash is important not only for determining the extent of the rights and obligations between the collateral taker and the collateral provider, but also affects the possibility of other financial collateral provider’s creditors to have their claims satisfied in insolvency proceedings. The classification of collateral in cash through the lens of legal consequences, which is used in the legal practice, does not reveal the peculiarities of this type of collateral, therefore the article will examine its other legally significant features. The article also analyses the causes of legal qualification errors and ways to eliminate them.
Keywords: finansinis užstatas pinigais; įkeitimas; prioritetas; kontrolė